2015
DOI: 10.1039/c5cp01799h
|View full text |Cite
|
Sign up to set email alerts
|

Role of hydration in phosphatidylcholine reverse micelle structure and gelation in cyclohexane: a molecular dynamics study

Abstract: In this work, we employ all-atom molecular dynamics simulations to examine the hydration response of phospholipid reverse micelles in cyclohexane. This ternary phospholipid-water-cyclohexane system is an important organogel forming system and the focus of this study is on gaining insight on the factors governing the gelation transition. We map the contributions rising from specific lipid-lipid and lipid-water interactions, and their response to increasing aggregate size and changes in water-to-lipid ratio. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 53 publications
4
22
0
Order By: Relevance
“…An overwhelming majority of computational studies of reverse micellar systems have focused on the anionic Aerosol OT surfactant (sodium bis-(2-ethylhexyl)sulfosuccinate) [37][38][39][40][41][42][43][44][45][46][47] . In re-cent years, however, there has been a surge of studies in which other surfactants and reverse micellar systems have been considered 21,[48][49][50][51][52][53][54][55][56][57][58][59][60] . Due to time-scale challenges, many of these studies have focused on preassembled aggregates, their structure, and the structure of confined water, while the self-assembly process and the resulting aggregate size distribution have been characterized only in a very few publications, see Refs.…”
Section: Introductionmentioning
confidence: 99%
“…An overwhelming majority of computational studies of reverse micellar systems have focused on the anionic Aerosol OT surfactant (sodium bis-(2-ethylhexyl)sulfosuccinate) [37][38][39][40][41][42][43][44][45][46][47] . In re-cent years, however, there has been a surge of studies in which other surfactants and reverse micellar systems have been considered 21,[48][49][50][51][52][53][54][55][56][57][58][59][60] . Due to time-scale challenges, many of these studies have focused on preassembled aggregates, their structure, and the structure of confined water, while the self-assembly process and the resulting aggregate size distribution have been characterized only in a very few publications, see Refs.…”
Section: Introductionmentioning
confidence: 99%
“…While reverse micelles of phospholipids have been rather extensively studied in various organic solvents, like cyclohexane, benzene or toluene (31)(32)(33), very few investigations have used oil as the nonpolar media (13,14,26,27). Nevertheless, both experimental results and simulations have shown that the nature of the media has a strong influence on the aggregation behavior of phospholipids (34)(35)(36)(37). Notably, vegetable oils can solubilize considerably more water than cyclohexane or the other solvents that have been more frequently studied in the literature (13,38,39).…”
Section: Introductionmentioning
confidence: 99%
“…They also studied the interactions governing lecithin aggregate morphology in cyclohexane in comparison to those in, e.g. heptane (37). Abel et al have examined phospholipid reverse micelle structure and dynamics in benzene via similar methodology (41).…”
Section: Introductionmentioning
confidence: 99%
“…We employ MD simulations with the umbrella sampling method to determine the adsorption conformations and energies of individual molecules on the Na-montmorillonite surface. As prior studies 22,[37][38][39][40][41] have raised concern on the performance accuracy of the aqueous environment force-field parametrizations used typically in atomistic detail MD simulations when taken to apolar solvent environments, we assess the modelling accuracy via density functional theory (DFT) electronic structure calculations with an implicit solvent model. The results enable an objective performance evaluation of the Charmm force field, in particular Charmm GenFF 42 parameters, for examining simple organic molecules in low dielectric, apolar solvent environments.…”
Section: Introductionmentioning
confidence: 99%